Pengaruh Latihan Power Otot Lengan Terhadap Kecepatan Pukulan Chudan Tsuki Pada Cabang Olahraga Bela Diri Karate - Lamusu, Zulkifli A.; Pou, Ganang (-, 2025)
This study aims to analyse the effect of arm muscle power training on the speed of chudan tsuki punches among fourth-semester students in the Physical Education Department of the Faculty of Sports and Health at Gorontalo State University. The method used was an experiment with a one-group pre-test post-test design involving 20 students as samples. The research instrument was a punch speed test measured using a stopwatch. The results of the study showed a significant increase in punch speed after the arm muscle power training intervention, which consisted of 16 sessions of push-ups. The average punch speed score increased from 29.6 in the pre-test to 41.4 in the post-test. The t-test yielded a calculated t-value of 31.89, which is greater than the critical t-value of 2.86 at a significance level of 0.05. Therefore, it can be concluded that arm muscle power training significantly affects the improvement in chudan tsuki punch speed.